Characterization and structural determination of a new anti-MET function-blocking antibody with binding epitope distinct from the ligand binding domain - Danielle M. DiCara (Nature Portfolio, 2017)
Abstract The growth and motility factor Hepatocyte Growth Factor/Scatter Factor (HGF/SF) and its receptor, the product of the MET proto-oncogene, promote invasion and metastasis of tumor cells and have been considered potential targets for cancer therapy. We generated a new Met-blocking antibody which binds outside the ligand-binding site, and determined the crystal structure of the Fab in complex with its target, which identifies the binding site as the Met Ig1 domain. The antibody, 107_A07, inhibited HGF/SF-induced cell migration and proliferation in vitro and inhibited growth of tumor xenografts in vivo. In biochemical assays, 107_A07 competes with both HGF/SF and its truncated splice variant NK1 for MET binding, despite the location of the antibody epitope on a domain (Ig1) not reported to bind NK1 or HGF/SF. Overlay of the Fab-MET crystal structure with the InternalinB-MET crystal structure shows that the 107_A07 Fab comes into close proximity with the HGF/SF-binding SEMA domain when MET is in the “compact”, InternalinB-bound conformation, but not when MET is in the “open” conformation. These findings provide further support for the importance of the “compact” conformation of the MET extracellular domain, and the relevance of this conformation to HGF/SF binding and signaling.